Sistem Pendukung Keputusan Pemilihan Obat Berdasarkan Gejala Penyakit Menggunakan Metode AHP - Ilham, Farizi; Sitio, Sartika Lina Mulani; Nardiono, Nardiono (SENTRI: Jurnal Riset Ilmiah, 2025)
The selection of appropriate medication based on the symptoms experienced by patients is a crucial aspect of healthcare services, particularly in clinics like Klinik K-24 that handle various complaints quickly and efficiently. A common issue encountered is the subjectivity in medication selection, which can lead to inappropriate therapy and potential unwanted side effects. To address this issue, a system is needed that can assist in making objective and structured decisions. This study aims to design and develop a Decision Support System (DSS) to assist doctors or medical personnel at Klinik K-24 in determining the most appropriate medication choices based on the symptoms reported by patients. The method used in this research is the Analytical Hierarchy Process (AHP), which breaks down complex problems into a hierarchical structure and then compares criteria and alternatives to generate priority weights. The decision-making criteria include the effectiveness of the medication for the symptoms, side effects, availability in the clinic pharmacy, and medication cost. The medication alternatives analyzed are based on common symptoms such as fever, cough, and sore throat. The system's results show that the AHP method can provide structured medication recommendations with an acceptable level of consistency (CR < 0.1). With this DSS, the medication selection process is expected to become faster, more accurate, and standardized, thereby supporting the efficiency of medical services at Klinik K-24.